2008
DOI: 10.1373/clinchem.2008.107029
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hepcidin-25 in Human Serum by Isotope Dilution Micro-HPLC–Tandem Mass Spectrometry

Abstract: To the Editor:Hepcidin-25, a liver-produced peptide hormone, was initially isolated from human urine and blood ultrafiltrate. Hepcidin-25 is thought to be the central regulator of iron metabolism (1 ). Iron deficiency is associated with low hepcidin-25 concentrations and anemia of chronic disease with high concentrations, but the true diagnostic value of hepcidin-25 is still under investigation. A recently published review (2 ) stated that only semiquantitative methods for comparative studies based on mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 5 publications
2
38
0
2
Order By: Relevance
“…In addition, Ganz et al (29 ) developed a competitive (c)ELISA for human serum hepcidin. Other groups have also reported reliable hepcidin assays that can be divided in 3 main methodologies: (a) MS (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95); (b) immunochemical assays, comprising cRIA (96,97 ), cELISA (13,29,98,99 ), and a 2-site ELISA (100 ); and (c) a ligand-binding assay (43 ) ( Table 1). Of the currently available commercial immunochemical research kits for serum hepcidin, we found the RIA and enzyme-immunoassay kits of Bachem (purchased November 2009 and August 2010, respectively) to be suitable to differentiate between hepcidin concentrations in serum samples of controls and patients with various iron disorders, whereas the bioactive hepcidin kit of DRG Instruments, (purchased October 2009) gave similar concentrations for all samples and could not discriminate between iron metabolism disorders (unpublished results).…”
Section: Second-generation (Quantitative) Hepcidin Assaysmentioning
confidence: 99%
“…In addition, Ganz et al (29 ) developed a competitive (c)ELISA for human serum hepcidin. Other groups have also reported reliable hepcidin assays that can be divided in 3 main methodologies: (a) MS (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95); (b) immunochemical assays, comprising cRIA (96,97 ), cELISA (13,29,98,99 ), and a 2-site ELISA (100 ); and (c) a ligand-binding assay (43 ) ( Table 1). Of the currently available commercial immunochemical research kits for serum hepcidin, we found the RIA and enzyme-immunoassay kits of Bachem (purchased November 2009 and August 2010, respectively) to be suitable to differentiate between hepcidin concentrations in serum samples of controls and patients with various iron disorders, whereas the bioactive hepcidin kit of DRG Instruments, (purchased October 2009) gave similar concentrations for all samples and could not discriminate between iron metabolism disorders (unpublished results).…”
Section: Second-generation (Quantitative) Hepcidin Assaysmentioning
confidence: 99%
“…16 Mass spectroscopic assays [17][18][19][20] and some immunoassays 21 using polyclonal Abs have been shown to reliably detect hepcidin but have limits in terms of cost, ease of transfer to a hospital laboratory setting, or scalability and reproducibility for assays involving polyclonal Abs. For this reason, we and others have developed sandwich enzyme-linked immunosorbent assays (ELISAs) using monoclonal Abs to detect hepcidin.…”
Section: Characterization Of Ab-binding Epitopes On Hepcidinmentioning
confidence: 99%
“…Some methods use an internal standard, either hepcidin analogs or bioactive hepcidin-25 synthesized with stable isotopes. [3][4][5][6][7][8][9][10] Recently, immunochemical (IC) assays for hepcidin-25 have also been developed, which comprise of competitive radioimmunoassays (RIA) 11 and enzyme-linked immunosorbent assays (ELISA). 12,13 Currently there is no reference method for hepcidin measurements.…”
Section: Introductionmentioning
confidence: 99%